Challenging A Contentious Discourse and Dismantling the False Divide through Multicultural Literature - Qutami, Mais Yusuf; Hamdan, Yousef Abdel Hafez (Dirasat: Human and Social Sciences, 2024)
Objectives: This study examines ways through which Eurocentric discourse can be challenged to combat inequality and discrimination against “the other.” The study also aims to demonstrate the positive impact that literature and cinema, with their diverse cultures, can have in teaching students how to question European central thought by understanding the lifestyle and worldview of “the Other,” highlighting their counter-narrative, and fostering empathy and tolerance toward “the other.” Methods: To achieve this purpose, Paulo Freire’s critical pedagogy was employed to equip English language students with critical thinking skills to critique facts. Works of multicultural literature and corresponding activities were chosen to enhance the ability to disrupt Eurocentric discourse. Students' responses were recorded and analyzed to track changes in empathy levels. Additionally, through critical and analytical readings of literary texts, the study sheds light on social disparities and criticizes oppressive structures that reinforce discrimination. Results: The study revealed ways to challenge Eurocentric discourse and resist discrimination against “the Other.” It also showed the positive role played by multicultural literary texts and cinema in training students to question European central discourse by exposing them to counter-narratives and the lifestyle of "the Other." The study further confirmed that increased awareness of injustice led to improved levels of empathy and tolerance towards others, inspiring a desire to contribute to social change. Conclusions: The study contributes to expanding knowledge about using multicultural literature and cinema in educating students about discrimination and combating Islamophobia and “the Other.” This is achieved by involving students in the process of liberating their minds through questioning European central discourse and the prevailing narrative of oppression, thereby enhancing their sense of empowerment, empathy, and tolerance.